The absence of functional bassoon at cone photoreceptor ribbon synapses affects signal transmission at Off cone bipolar cell contacts in mouse retina - Babai, Norbert; von Wittgenstein, Julia; Gierke, Kaspar; Brandstätter, Johann Helmut; Feigenspan, Andreas (Acta Physiologica, 2020)
Aim: Off cone bipolar cells of the mammalian retina connect to cone photoreceptor synaptic terminals via non-invaginating flat contacts at a considerable distance from the only established neurotransmitter release site so far, the synaptic ribbon. Diffusion from the ribbon synaptic active zone is considered the most likely mechanism for the neurotransmitter glutamate to reach postsynaptic receptors on the dendritic tips of Off cone bipolar cells. We used a mutant mouse with functionally impaired photoreceptor ribbon synapses to investigate the importance of intact ribbon synaptic active zones for signal transmission at Off cone bipolar cell contacts. Methods: Whole-cell patch-clamp recordings from Off cone bipolar cells in a horizontal slice preparation of wildtype (Bsnwt) and mutant (BsnΔEx4/5) mouse retina were applied to investigate signal transmission between cone photoreceptors and Off cone bipolar cells. The distribution of postsynaptic glutamate receptors in Off cone bipolar cell dendrites was studied using multiplex immunocytochemistry. Results: Tonic synaptic activity and evoked release were significantly reduced in mutant animals. Vesicle replenishment rates and the size of the readily releasable pool were likewise decreased. The precisely timed transient current response to light offset changed to a sustained response in the mutant, exemplified by random release events only loosely time-locked to the stimulus. The kainate receptor distribution in postsynaptic Off cone bipolar cell dendritic contacts in BsnΔEx4/5 mice was largely disturbed. Conclusion: Our results suggest a major role of functional ribbon synaptic active zones for signal transmission and postsynaptic glutamate receptor organization at flat Off cone bipolar cell contacts.
CRIS-Team Scopus Importer:2020-12-11
Keywords: Bassoon; cone photoreceptor; Off cone bipolar cell; retina; ribbon synapse; signal transmission